Istilah sains dalam bahasa Melayu: usaha memperkaya dan mengupayakannya (Jurnal Bahasa, 2001)
The Malay Language has gone through many developments. Among them is its development as a language of science. The aspect of the development of Malay as the language of knowledge is intimately connected with the creation and development of science vocabulary. This article attempts to trace the aspect of creation of science terms and the efforts undertaken to enrich the science vocabulary and thus making the science terms created capable.